Strategic Staffing? How Performance Pressures Affect the Distribution of Teachers Within Schools and Resulting Student Achievement. (December 2017) - Grissom, Jason A.; Kalogrides, Demetra; Loeb, Susanna
School performance pressures apply disproportionately to tested grades and subjects. Using longitudinal administrative data—including achievement data from untested grades—and teacher survey data from a large urban district, we examine schools' responses to those pressures in assigning teachers to high-stakes and low-stakes classrooms. We find that teachers with more positive performance measures in both tested and untested classrooms are more likely to be placed in a tested classroom in the following year. Performance measures even more strongly predict a high-stakes teaching assignment in schools with low state accountability grades and where principals exercise more assignment influence. In elementary schools, we show that such "strategic" teacher assignment disadvantages early grades, concentrating less effective teachers in K–2 classrooms. Reassignment of ineffective upper-grades teachers to early grades systematically results in lower K–2 math and reading achievement gains. Moreover, evidence suggests that students' lower early-grades achievement persists into subsequent tested grades.